Aquatic insects as biological indicator in biomonitoring freshwater health - Ab Hamid, Suhaila; Wan Abd Ghani, Wan Mohd Hafezul; Abdul, Nurul Huda; Hashim, Nur Aida (Department of Wildlife and National Parks (PERHILITAN) Peninsular Malaysia, 2023)
Insects have been extensively studied, but yet little attention has been given to aquatic insects. Aquatic insects live in some part or entirely of their life cycle in water. Different kinds of aquatic insects reside in different types of freshwater environments. Therefore, aquatic insects have become a diverse group of insect species that adapt to various habitats. Aquatic insects have a significant role in freshwater ecosystems, particularly as a food source for most predators found in aquatic and forest ecosystems, especially fish, amphibians, birds, and bats. In helping to balance the freshwater ecosystem, aquatic insects have different feeding habits, which is important so that aquatic systems can support an inclusive variety of organisms. Their detritivorous, grazing behaviours, and predator-prey interactions have a high impact on the nutrient dynamics of the aquatic environment. Besides, aquatic insects adapted very well to the changes in both lotic and lentic systems and showed a high sensitivity for detecting early changes in their geographical area, thus making them the most reliable indicators of water quality. Nevertheless, aquatic insects offer a spectrum of responses to different types of pollution in aquatic water bodies over time and places. Regarding this, the use of aquatic insects as biological indicators in water health biomonitoring receive close attention from scientists worldwide. Therefore, this chapter focuses on the roles of aquatic insects as one of the most reliable indicators in monitoring the health or quality of freshwater ecosystems.